Inflammation in common variable immunodeficiency is associated with a distinct CD8+ response to cytomegalovirus - Marashi, Sayed Mahdi (2011)
BACKGROUND: Common variable immunodeficiency is the most common primary immunodeficiency. A subset of patients suffers from debilitating inflammatory complications. OBJECTIVES: We investigated the role of cytomegalovirus, and the T cell response targeted at this virus, in this inflammatory disease. METHODS: Phenotypic and functional assays were used to profile CMV specific T cells in common variable immunodeficiency patients with and without inflammatory complications. Highly sensitive immunohistochemistry was used to detect cytomegalovirus antigens at sites of inflammation. RESULTS: Cytomegalovirus was significantly associated with inflammatory disease, which occurred in 31/43 (72%) virus-exposed patients and 8/31 (26%) naïve patients (p=0.0001). Cytomegalovirus pp65-NLV epitope specific CD8+ T-cell frequencies were significantly elevated in inflammatory patients but these cells did not show evidence of exhaustion, with low levels of PD-1 and high T cell receptor avidity. Rather, they showed features consistent with high in vivo functionality and proliferative activity including reduced levels of the anti-inflammatory marker CD73 (1.67% NLV+ cells were CD73+ vs 42.01% in non inflammatory patients p=0.004) and increased Ki-67 expression (37% vs 2% in non-inflammatory patients. p<0.0001). In vitro, the cytomegalovirus specific T cells showed high antigen specific proliferative potential compared to cells from non inflammatory patients. Using sensitive immunohistochemistry we detected for the first time viral antigen at the sites of inflammation, indicative of active viral replication. CONCLUSIONS: Our data strongly support a direct role for cytomegalovirus and a hyper-reactive cytomegalovirus specific immune response, in the debilitating chronic inflammatory complications of common variable immunodeficiency.